Electrochemical performance of Mo doped high voltage spinel cathode material for lithium-ion battery. (February 2018) - Kazda, T.; Vondrák, J.; Visintin, A.; Sedlaříková, M.; Tichý, J.; Čudek, P.
Highlights: Firs report about Mo-doped LiNi0.5 Mn1.5 O4 cathode synthesized by solid state reaction. Influence of Mo-doping to the thermal and structural stability was observed. Mo-doped electrode provides higher capacity at 0.5C–125 mAh/g compare to 115 mAh/g. Mo-doped sample lost 4.7% of capacity compare to 19.6% at 50 °C cycling. Abstract: This article deals with the properties of high-voltage cathode material LiNi0.5 Mn1.5 O4 synthesized by a solid-state reaction method and the influence of doping this material by molybdenum. The samples – LiMo x + y Ni0.5 - x Mn1.5 - y O4 with different Mo contents ( x = 0.00, 0.05, y = 0.00, 0.05) were successfully synthesized by two step annealing process and they were then investigated by SEM, EDS spectroscopy, thermo gravimetric analysis, cyclic voltammetry and charge–discharge tests at different loads and high temperature in lithium-ion cells with metal lithium as a counter electrode. Results showed that the initial discharge capacity and capacity during high temperature cycling of the LiMox + y Ni0.5 - x Mn1.5 - y O4 cathode were improved with addition of Mo when x = 0.05. Thermal analysis results suggested that the Mo doping slightly improved the stability of the crystal structure of the LiNi0.5 Mn1.5 O4 cathode which leads to an improved stability during high temperature galvanostatic cycling.